Simulation of internal waves using GM model and comparison against measurements during ARMEX-I - KUMAR, G. V. KRISHNA; SWAIN, J. (MAUSAM, 2005)
A linear internal wave model based on the Garrett-Munk (hereafter GM) modal spectrum has been developed. The model simulates sound speed structure due to internal waves in the ocean. CTD yoyo (go up and down continuously) data collected during the ARMEX-I experiment has been utilized to validate the model. Internal waves amplitudes at the experimental site are found to be >1m. EOF and modal decomposition analyses reveal that the modal bandwidth parameter j* = 3 and modal energy damping parameter P = 1 or 2 and follows the GM suggested values. Comparison of the measured sound speed profiles against the simulated reveals that the GM model is capable of reproducing most of the variability due to IW in the deep-waters. The agreement between the observed and simulated perturbations is quite good.